Mağallaẗ kulliyyaẗ al-Maʿrīf al-ğāmiʿaẗ (AlMaarif University College, 1998)
Devoted to research and scholarship in Law, Arabic, Islamic law, English language and literature, management, financial science, economics, and physical (sports) education and physical knowledge.
Keywords: Electronic journals; Social Sciences : Periodicals; Humanities : Periodicals; Islamic law; Economics; Iraq